THU0448 Safety competences knowledge and behavioural skills of patients treated by biologics in rheumatology. (23rd January 2014) - Rat, A.-C.; Fautrel, B.; Flipon, E.; Gossec, L.; Caritey, B.-D.; Margerie, L.; Nataf, H.; Piperno, M.; Pallot Prades, B.; Poilvert, R.M.; Royant, V.; Sadji, F.; et al.
Abstract : Background: Biologics are known to entail specific risks; therefore teaching patients safety competences and what decisions to take in some situations is necessary. The level of knowledge of safety competences are not well known in patients treated by biologics. Objectives: The objective was to describe the safety competences of a representative sample of patients treated by biologics for inflammatory arthritis in order to find which ones should be better highlighted. Methods: Data were obtained from a national cross-sectional survey. Rheumatologists were randomly sampled from the national directory. They were invited to include 3 to 5 consecutive patients treated by biologics whatever their inflammatory arthritis diagnosis. All patients completed a 54-item questionnaire addressing safety competences and sociodemographic, types of information received, quality of life and coping style data. The questionnaire to measure knowledge and skills regarding biologics was developed by health professional and patients using 3 steps: elaboration of a comprehensive list of competences, selection via a Delphi technique, elaboration of a questionnaire for the 26 competences selected. The questionnaire includes a series of multiple-choice questions on knowledge and on clinical situations grouped in dimensions*. Results: Of the 671 patients included, 67% were women, 62% had RA and 38% spondylarthritis, 63% were treated by subcutaneous antiTNF. The mean age was 53±13 years old. Patients received information during a medical consultation (90%), a consultation with a nurse (30%), with a written booklet (59%) and during a therapeutic education program (11%). The median total score (sum of the items)was 39 (range 1-53).Knowledge questions had not higher percentages of correct answers than behavioural skills items. Scores and number (%) of patients with a number of correct answers lower than 50% are described in the table. For pregnancy score, 42% of women and 66% of men answered incorrectly to the 2 items.The Scores are the sums of item Conclusions: Safety competences of patients under biologics can be improved. There is a need for patient education and counselling to improve security and behavioural skills in biologic-treated patients References: L Gossec. Ann Rheum Dis 2010;69(Suppl3):476 Disclosure of Interest: None Declared